O esporte paralímpico no Brasil: do amadorismo ao profissionalismo - Godoy, Mariana Rodrigues Bighetti [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
At the beginning of the 20th century it was created the Paralympic Movement with the objective of rehabilitating war fighters who have had spinal cord injuries, through spaces of activities and adapted sport practices. In its first stage people with disability who participated in the events were needed wheelchair, but over the years other deficiencies were included, such as visual, auditory, intellectual and amputees. The events focused on rehabilitation and participation have lost space for high income exercises and the aim for results. The consequence of a system of organization of the sport for people with disabilities started becoming institutionalized and professional. It has developed the technology, the rules and the management of the games culminating in the big event called Paralympic Games. In this perspective, how have this movement happened in Brazil? What are the impacts on society? And What about the legacies and movements in the country after the Rio 2016 Paralympic Games? This present study aims to answer these questions, based on a literature research, which reveals the Paralympic Sport trajectory in Brazil, and through literature and existing documents to analyze the evolution and the challenges of Brazil in this subject. The results of the Paralympic sport at the competitive level are impressive as a result of investment, planning and organization. But the challenge is to go further, and also invest in education and leisure, after all, sports practices are not only for high income, but it is everyone's right

No início do século XX tivemos o fenômeno nomeado de Movimento Paralímpico. Começou com o objetivo de reabilitar combatentes de guerra com lesões medulares, por meio de espaços de atividades e práticas esportivas adaptadas. Na sua primeira etapa as pessoas com deficiência que participavam dos eventos eram cadeirantes, com o passar dos anos foram incluindo outras deficiências, como a visual, auditiva, intelectual e amputados. Os eventos com foco na reabilitação e participação perdem espaço para o alto rendimento e a busca por resultado. Consequência de um sistema de organização do esporte para pessoas com deficiência foi se institucionalizando e se profissionalizando. Desenvolveu a tecnologia, as regras e a gestão dos jogos culminando no megaevento Jogos Paralímpicos. Nesta perspectiva, como aconteceu esse movimento no Brasil? Quais os impactos na sociedade? E os legados e manifestação no país após receber o Jogos Paralímpicos Rio 2016. O presente estudo visa responder a tais questionamento, através de uma pesquisa bibliográfica, revelando a trajetória do Esporte Paralímpico no país, e através da literatura e documentos existentes analisando a evolução e os desafios do Brasil neste tema. Os resultados do esporte paralímpico no nível competitivo são impressionantes, consequência de investimento, planejamento e organização. Mas o desafio é ir além, e investir também na educação e lazer, afinal as práticas desportivas não são apenas para o alto rendimento, mas é direito de todos
Keywords: Paralimpíadas; Esportes - Brasil; Jogos; Games